PENYULUHAN TENTANG PENTINGNYA HUKUM SEBAGAI KERANGKA KEHIDUPAN SOSIAL (LIVING LAW) PADA MASYARAKAT SEKITAR MA'HAD AL-ZAYTUN - Rahim, Abdur; Hizbullah, Diva; Dewanti, Tri Mustika; Nursabila Isu, Mutimah; Gumilang, Ibnu Fajar; Marjuki, Ali; Ramadhani, Ahmad Mulki; Suryana, Nanang (Jurnal Abdimas Bina Bangsa, 2024)
Law has a very important role in forming the framework of social life in society. In the context of Ma'had Al-Zaytun, law not only functions as a tool of enforcement, but also as a moral and ethical guideline that regulates interactions between individuals in society. Counseling about law as a framework for social life in the community around Ma'had Al-Zaytun is very important to increase legal awareness and create a harmonious social order. This Community Service (PkM) discusses the importance of understanding law in a social context, the counseling methods used in the community around Ma'had Al-Zaytun, as well as the expected impact of this activity. The results of this Community Service (PkM) outreach activity show that the law functions as a regulator of social behavior, a conflict mediator, and a link between local values ​​and broader legal norms.